Three-Dimensional-Printed Guiding Template for Unicompartmental Knee Arthroplasty - Gu, Fei (Biomed Res Int, 2020)
BACKGROUND: For unicompartmental knee arthroplasty (UKA), accurate alignment of the limb is crucial. This study is aimed at investigating the efficacy and safety of a three-dimensional printed patient-customized guiding template (3DGT) for UKA. METHODS: A total of 22 patients receiving UKA were randomly divided into the 3DGT-UKA group (n = 11) and traditional UKA group (T-UKA group; n = 11). In the 3DGT-UKA group, the line and angle of osteotomy were decided on a 3D image of the limb reconstructed from imaging data; a guiding template was then designed and printed out. The patients in the T-UKA group underwent conventional UKA. Prosthesis size, operation time, postoperative drainage, hip–knee angle (HKA), pain, and Hospital for Special Surgery (HSS) scores were recorded at day 1, week 1, month 1, and month 3 after surgery. RESULTS: There was no significant difference in the size of prostheses between the preoperatively designed and actually used in the 3DGT-UKA group (p > 0.05). HKA was comparable in 3DGT-UKA and T-UKA patients. Operation time was shorter (53.6 ± 6.4 minutes vs. 75.8 ± 7.1 minutes) and wound drainage was less (93.2 ± 3.9 mL vs. 85.2 ± 3.0 mL) in 3DGT-UKA than in T-UKA (p < 0.05). Hospital stay was shorter in the 3DGT-UKA group. The 3DGT-UKA group had a lower VAS score on day 1, week 1, and month 1 and a higher HSS score on week 1 and month 1 after surgery. No varus/valgus deformity or prosthesis loosening was observed in either group at the final follow-up. CONCLUSION: The 3D-printed patient-customized guiding template may help decrease operation time, decrease blood loss, and improve short-term clinical outcomes in patients undergoing UKA surgery.